PRODUKSI MINYAK SAWIT MENTAH DAN ANTIOKSIDAN SECARA SIMULTAN DENGAN METODE AQUEOUS ENZYME-ASSITED OIL EXTRACTION MENGGUNAKAN ENZIM YANG DIPRODUKSI DARI FERMENTASI SUBSTRAT PADAT OLEH ASPERGILLUS NIGER - Najmi Mardhotillah, Titian
Plantations in Indonesian are dominated by oil palm. The majority of oil palm plantations are owned by Private Large Plantations (PBS), then People's Plantations (PR), and finally State Large Plantations (PBN). The smallholder oil palm plantations (PR) are very far behind of the large plantations, so the development of CPO production through a “biochemical platform” namely aqueous enzyme-assisted oil extraction as the basis for bio-industrial development with the economy of production scale at relatively small which is a promising process technology to be implemented on small holder oil palm plantation. The purpose of this study was to produce and to determine the activity of cellulase, pectinase, and tanase enzymes from solid substrate fermentation by Aspergillus niger, as well as to evaluate the effectivenes of using crude enzymes in the aqueous enzyme-assisted oil extraction of palm fruit on the recovery of CPO. The FFA and antioxidant contents, the activity antioxidants ie. phenolic, beta-carotene, tocopherol contained in crude palm oil (CPO) produced were also determined. Variations for enzyme production are the time periods of fermentation wich are 3, 5, and 7 days. The results showed the optimum crude enzyme activity was on the fermentation periods of 5 days with cellulase activity 0.26 U/mL, pectinase 0.47 U/mL, tanase 0.14 U/mL. The use of enzymes increased the extraction yield of CPO and was optimum on the fermentation periods of 5 days with a yield of 79,84% (g/g total oil in the mesocarp). The use of enzymes has an increasing effect on the antioxidant content of CPO and was optimum on the fermentation periods of 5 days with phenolic content of 47.07 mg GAE/kg oil, ?-tocopherol 67 ppm, beta-carotene 831.88 ppm, and antioxidant activity 366.03 mg Trolox/kg of oil. The use of enzymes gave CPO with quality according to SNI 01-2901-2006, and optimum on the fermentation periods of 5 days with free fatty acid value of 4.61%.